Active Cardboard Packaging With Encapsulated Essential Oils for Enhancing the Shelf Life of Fruit and Vegetables - López–Gómez, Antonio; Ros–Chumillas, María; Buendía-Moreno, Laura; Martínez–Hernández, Ginés Benito (Frontiers in Nutrition, 2020)
The quality loss of fruit and vegetables should be minimized to reduce food waste during retail. In that sense, sustainable and effective postharvest techniques/technologies are needed, showing active packaging including encapsulated essential oils a high potential. In that sense, we studied the effect of different sized active packages (including β-cyclodextrin-EOs inclusion complex) on the quality of grapes, nectarines and lettuces (as models of berry fruit, stone fruit and leafy vegetables) during storage at 2 ºC (90-95% relative humidity). The active industrial tray showed the best effect on grapes and lettuce quality, since it reduced rachis dehydration and product weight loss (reduced by ≈50% in grapes after 30 days), reduced berry shatter (reduced by ≈40% in grapes after 30 days), highly maintained the physicochemical quality (soluble solids content, titratable acidity and firmness) and also reduced microbial growth (0.5-1.4 lower log units than non-active industrial tray). For nectarines, the package with the biggest active surface (large tray, 200×300×90) also showed the best quality retention compared to smaller packages, showing nectarines within active large tray better microbial quality (0.6-1 lower log units than non-active large tray) and firmness. As expected, flow-packaging of nectarines (using active trays) better controlled the product weight loss. In conclusion, active cardboard packages with greater active surface better preserved quality of grapes, nectarines and lettuce, which sensory quality was accepted after more than 30, 25 and 14 days at 2 ºC, contrary to non-active samples (approximately 1 week less).